Capital Strengthening Strategies In Fulfilling Regulations Ojk At Pt Bank Bengkulu - Alfajri, Amad Zaki; Kamaludin, Kamaludin; Rusdi, Muhammad (UNIB Press, 2023)
This study aims to determine the strategy of strengthening the fulfillment of capital at PT Bank Bengkulu.This type of research uses a quantitative descriptive approach with a survey method.The data to be used in this research is primary data obtained directly from respondents of PT Bank Bengkulu employees who were taken through distributing questionnaires online and also interview data with several expert sources.The data analysis method used descriptive analysis and SWOT analysis.The results showed that:(1)The results of the analysis of internal strategic factors show that the factors that become the main strengths of PT Bank Bengkulu are owned by the local government On the other hand,the factors that become the main weaknesses of PT Bank Bengkulu in fulfilling the minimum core capital are business models that tend to be conventional (fee-based income that still contributes less);(2)The results of the analysis of external strategic factors show that the factors that become the main opportunities for PT Bank Bengkulu in fulfilling the minimum core capital are forming a Joint Business Group (KUB) as stipulated in POJK No. 12 of 2020.On the other hand, the main threat factor for PT Bank Bengkulu in fulfilling the minimum core capital is the uncertainty of regional economic growth which has the potential to reduce the capital deposit of each region(series A shareholders) and (3) The priority strategy that can be implemented by PT Bank Bengkulu in order to fulfill the minimum core capital in accordance with OJK regulations is the W-O strategy